Gynecologic and breast cancers in women after exposure to blue Asbestos at Wittenoom - Reid, Alison; Segal, A.; Heyworth, J.; De Klerk, N.; Musk, A. (American Association for Cancer Research Inc, 2009)
Introduction: Animal studies have suggested an association between asbestos and ovarian cancer, and asbestos fibers have been detected in human ovaries. Sexual intercourse may introduce asbestos fibers into the vagina and to the cervix and ovaries. Occupational cohorts have reported excess mortality from reproductive cancers, but exposure-response relationships are inconsistent. We examine the incidence and exposure-response relationships of these cancers among 2,968 women and girls exposed to blue asbestos at Wittenoom, Western Australia. Methods: 2,552 women were residents of the town and 416 worked for the asbestos company (Australian Blue Asbestos). Standardized incidence ratios compared the Wittenoom women with the Western Australian population. A nested case-control design and conditional logistic regression examined exposure-response relationships. Results: Ovarian (standardized incidence ratio, 1.27), cervical (standardized incidence ratio, 1.44), and uterine cancer (standardized incidence ratio, 1.23) increased but not statistically significantly among the Wittenoom women compared with the Western Australian population. Among the Australian Blue Asbestos workers, cervical cancer was twice that of the Western Australian population (standardized incidence ratio, 2.38), but ovarian cancer was less (standardized incidence ratio, 0.65). Women who first arrived at Wittenoom aged =40 years had an odds ratio of 13.9 (95% confidence interval, 2.2-90.2) for cervical cancer compared with those aged <15 years at first arrival. Women who lived with or washed the clothes of an Australian Blue Asbestos worker did not have an increased risk for any of the gynecologic or breast cancers. Discussion: There is no consistent evidence of an increased risk for gynecologic and breast cancers among the women from Wittenoom. Ovarian cancers and peritoneal mesotheliomas were not misclassified in this cohort. Copyright © 2009 American Association for Cancer Research.